Holomorphic Fock spaces for positive linear transformations - Fabec, R.; Ólafsson, G.; Sengupta, A.N. (Mathematica Scandinavica, 2006)
Suppose $A$ is a positive real linear transformation on a finite dimensional complex inner product space $V$. The reproducing kernel for the Fock space of square integrable holomorphic functions on $V$ relative to the Gaussian measure $dμ_A(z)=\frac {\sqrt{\det A}} {π^n}e^{-\Re\langle Az,z\rangle}\,dz$ is described in terms of the linear and antilinear decomposition of the linear operator $A$. Moreover, if $A$ commutes with a conjugation on $V$, then a restriction mapping to the real vectors in $V$ is polarized to obtain a Segal-Bargmann transform, which we also study in the Gaussian-measure setting.